The Law Enforcement Weakness of Songs and Musics Copyright Crimes - Edi Tuahta Putra Saragih; Muhammad Citra Ramadhan; Isnaini Isnaini (Universitas Negeri Gorontalo, 2021)
This research aimed to: (a) obtain the forms of copyright infringement of songs and/or music (with or without lyrics); (b) understand the role of the police, in this case the Police Precinct, in the law enforcement; (c) identify the factors that influenced the law enforcement. The research method used the normative-empirical legal research, with the initial stages of specifying norms in order to get the proper picture, and then specifying empirical events in order to get the real picture. The research results showed several matters: 1) The forms of copyright infringement of songs and/or music (with or without lyrics) found included: the distribution of the works or the copies, the performances of the works, and the announcements of the works; 2) Police Precinct did notultimately carry out their role as a law enforcer for the copyright infringement of songs and/or music (with or without lyrics); and 3) The factors that influenced the law enforcement on the copyright infringement of songs and/or music (with or without lyrics), namely: legislation factor, in the matter of complaint offenses; law enforcement factor, in terms of the capacity of members; less supportive factor of facilities and infrastructure; legal awareness factor, in the problem of the lack of legal counseling; and cultural factor, related to the differences in norms in the copyright law between those in society and those in regulations.